SPM Receptor Expression and Localization in Irradiated Salivary Glands. (August 2021) - dos Santos, Harim Tavares; Nam, Kihoon; Hunt, Jason P.; Buchmann, Luke O.; Monroe, Marcus M.; Baker, Olga J.
Radiation therapy–mediated salivary gland destruction is characterized by increased inflammatory cell infiltration and fibrosis, both of which ultimately lead to salivary gland hypofunction. However, current treatments (e.g., artificial saliva and sialagogues) only promote temporary relief of symptoms. As such, developing alternative measures against radiation damage is critical for restoring salivary gland structure and function. One promising option for managing radiation therapy–mediated damage in salivary glands is by activation of specialized proresolving lipid mediator receptors due to their demonstrated role in resolution of inflammation and fibrosis in many tissues. Nonetheless, little is known about the presence and function of these receptors in healthy and/or irradiated salivary glands. Therefore, the goal of this study was to detect whether these specialized proresolving lipid mediator receptors are expressed in healthy salivary glands and, if so, if they are maintained after radiation therapy–mediated damage. Our results indicate that specialized proresolving lipid mediator receptors are heterogeneously expressed in inflammatory as well as in acinar and ductal cells within human submandibular glands and that their expression persists after radiation therapy. These findings suggest that epithelial cells as well as resident immune cells represent potential targets for modulation of resolution of inflammation and fibrosis in irradiated salivary glands.